Incorporation of CdSe quantum dots (QDs) in KH2PO4 (KDP) crystalline host: Processes of elaboration and characterization - Samyia, Addala (Université de M'sila, 2018)
The aim of this work is to survey experimentally the effect of doping CdSe quantum dots (QDs) on structural and optical properties of Di-hydrogen phosphate KH2PO4 (KDP) single crystal, where we expose a simple and reproduced technic to obtain KDP:CdSe single crystal starting from aqueous solution phase. In order to characterize the samples comfortably, the obtained crystals were cleaved into pellets with suitable size each surface being parallel to the faces (100). The XRD results denote that the CdSe QDs inside KDP single crystal have only one preferred direction (110) and the estimated size as derived from Sheere’s formula proved the nano-regime of guest material. On the other side, UV–vis absorption spectrums appear that a pure KDP crystal has transparence property in the visible range with a large window where Eg (KDP) ≈ 7.17 eV. However, KDP:CdSe sample exhibits two bands located at 425 nm and 625 nm attributed to the transition band to band and excitonic, respectively. As an accordance result, photoluminescence (PL) measurements indicate that the band gap of CdSe QDs inside KDP single crystal appears a significant amount of blue-shift ( Eg = 0.284 eV) due to well recognized quantum confinement effect exerted by the CdSe QDs. Published by Elsevier GmbH.
Keywords: CdSe QDs KDP XRD UV–visible Photoluminescence